Total Kadar Bilirubin Pada Pasien Tuberculosis (TB) Paru Setelah 5 Bulan Mengkonsumsi Obat Anti Tuberkulosis (OAT) di Rumah Sakit Tentara Kota Binjai - Fani Nuryana Manihuruk; Sanna Kamisna Purba; Liber Napitupulu (Herbal Medicine Journal, 2022)
Pulmonary tuberculosis (TB) is an infectious disease caused by Mycobacterium tuberculosis which attacks the lungs and bronchi. Anti-tuberculosis drugs consist of isoniazid, ethambutol, pyrazinamide, rifampicin and streptomycin which must be consumed for 6 months. OAT has side effects, especially disturbing liver function, one of which is bilirubin. Bilirubin is a yellow pigment derived from the heme reshuffle of hemoglobin in the process of erythrocyte breakdown by reticuloendothelial cells. This research is desktiptif. This study aims to describe the total bilirubin levels in pulmonary tuberculosis patients after 5 months of consuming anti-tuberculosis drugs in TK.IV.01.07.02 Binjai Army Hospital in May-June. This study was taken from 53 samples of total bilirubin levels in tuberculosis patients who had consumed OAT for 5 months. The results of the 53 samples found normal total bilirubin levels of (77.40%) and increased by (22.60%). Frequency distribution in male sex (56.6%) women (43.4%). Total bilirubin levels increased more in male patients (13.21%). The increase in total bilirubin occurred at> 56 years of age. Total bilirubin levels increased more in female patients (9.43%).